Short Communication: Georeferencing orchids specimen history cards in Bogor Botanic Gardens to increase their use for conservation efforts - EKA MARTHA DELLA RAHAYU; SAFRAN YUSRI (Society for Indonesian Biodiversity, 2016)
Rahayu EMD, Yusri S. 2016. Georeferencing orchids specimen history cards in Bogor Botanic Gardens to increase their use for conservation efforts. Biodiversitas 17: 510-514. Orchids are considered valuable plant resource but overharvesting and habitat conversion have threatened their population. Bogor Botanic Gardens (Kebun Raya Bogor; BBG) stores millions of plant specimens, including orchids, taken from the wild or captivity. Origin of specimens is recorded in specimen tags and cards, where each of these can be converted to species occurrence datum for investigations of biodiversity, its relationship with the environment, evaluating conservation efforts and anthropogenic disturbances along spatial or temporal scales. However, data from tags and cards available are often insufficient because localities are typically being recorded as textual descriptions, without geographic coordinates, thus making analysis using Geographical Information System (GIS) tools difficult. In this paper, we reviewed the use of online resources (i.e. GoogleMapsâ„¢, ProtectedPlanet.net) for georeferencing specimen cards and Quantum GIS as a GIS tool to store and display the data. Specimen cards from the chosen genera of orchid in BBG were reviewed. The georeferencing process encountered several obstacles, includes: geographically biased locations, changes in spatial-administrative borders, unregistered location name, unavailability of location name in online resources, and typographic errors during specimen recording process. We also encounter quality difference along georeferenced records, some are good quality (i.e. record coordinates or nearest village) and some are poor (only record the provinces). Georeferencing is an underappreciated task, but once it is done, it can be used for future expeditionary research, national conservation planning, species status review, and other large scale analysis for both spatial and temporal scales.